Behind Plantation Supervision: The Dynamics of Coffee Roasting Practices in Bojongrejo Temanggung 1970s-2000s. - Nalia Dhofatul Addana; Carolina Santi Muji Utami (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study examines the relationship between the monitoring system and coffee harvesting in the Bojongrejo Temanggung coffee plantation, which took place during the 1970s-2000s. Coffee harvesting is the activity of picking and collecting coffee that has fallen and scattered on the harvested plantation land. This study uses historical methods (heuristics, criticism, interpretation, and historiography) based on oral history sources and through a socio-economic approach. Based on the research findings, it shows that the plantation monitoring system is run through a hierarchical management structure, but in its implementation still leaves leeway in plantation spaces that can be used for coffee harvesting by the surrounding community. When coffee production was high (boom period) from the 1970s to the 1990s, massive coffee harvesting activities occurred in the Bojongrejo coffee plantation. Coffee harvesting was used as an informal economic strategy by the surrounding community and took place as a collective habit, especially for women. Based on this, the massive coffee gorek creates a local economic network that operates outside the official plantation distribution system and changes according to the dynamics of plantation production. The results of this study also confirm that informal economic practices do not always arise solely due to economic crises, but are also driven by high production opportunities and inconsistent supervision, which emerge as a rational expression of the community's moral economy, not simply institutional weaknesses.